Multi-Energy Complementary Absorption Heat Pump Applied for Combined Cooling and Heating over a Wide Temperature Range - Lu Ding; Liu Zijian; Shen Tao; Chen Rundong; Gong Maoqiong (Zhileng xuebao)
Achieving low-carbon combined cooling and heating supply in distributed areas away from centralized cooling and heating networks is highly significant in the context of carbon neutrality. This study proposes a combined cooling and heating system based on an absorption heat pump, which uses a variety of clean and renewable energies, such as solar heat, geothermal, waste heat, biomass, and air-source energy, to achieve the combined cooling and heating in a wide temperature range from -20 ℃ to 90 ℃. Such systems are suitable for distributed areas, such as villages, cities, and industrial parks. The system model was constructed based on Aspen, and a prototype was developed. The prototype uses a vacuum tube collector to capture solar thermal energy and introduces natural gas as a supplementary heat source to balance fluctuations of solar energy. Multiple sets of indoor heating and cooling terminals can be driven through medium circulation and valve switching using a single set of absorption heat pumps and outdoor units. The environmental test of the prototype was performed in Jinan, and the solar thermal ratio reached 35% during the testing period. An all-weather stable energy supply was achieved by proportional control of natural gas. Moreover, a wide range of concentration adjustments was achieved by controlling the liquid level in the solution tank, enabling efficient system operation in a wider temperature range. The coefficient of performance (COP) of cooling reached 0.30-0.43 at -20 ℃ and 0.70-0.78 at 7 ℃, with cooling water temperatures varying from 30 ℃ to 20 ℃; the COP of heating reached 1.40-1.90 at 45 ℃ and 1.35-1.56 at 80 ℃, with evaporation temperature varying from -15 ℃ to 20 ℃. The study results demonstrated that introducing solar thermal energy and ambient energy recovery increased the fraction of renewable energy in the system to over 50%. Compared with the traditional method of gas furnace plus air conditioning, the annual operating cost and carbon emissions of the proposed system were reduced by over 54.3% and 44%, respectively, which has significant application potential.